The Role of Stenting in Aortic, Renal, and Mesenteric Occlusions - Nichols, Emma Hitt (MD Conference Express, 2014)
Percutaneous stenting can be an effective approach for the treatment of various types of occlusive arterial disease; however, appropriate patient selection is critical.